Cinnamaldehyde for the Prevention and Control of Foodborne Pathogens and Their Biofilms: a Review of Research and Applications - DU Xueying, HU Xin, FENG Zeyin, SUN Jing, LI Xiangfei, PANG Xinyi, LU Yingjian (Shipin Kexue)
Foodborne pathogens exist primarily as biofilms in the food processing environment. Different from planktonic bacteria, biofilm has a complex structure, strong adhesion and high resistance to conventional disinfection methods. Cinnamaldehyde, a plant-derived compound, has garnered widespread attention as a new strategy for combating foodborne pathogen biofilms due to its broad-spectrum antibacterial activity and significant inhibitory effect on biofilm. This paper summarizes recent progress in research on cinnamaldehyde’s antibacterial and anti-biofilm effects on common foodborne pathogens. The underlying mechanism of action is systematically analyzed from three aspects: anti-bacterial adhesion, antibacterial and anti-quorum sensing effects. Furthermore, the application of nanoscale cinnamaldehyde as antibacterial agent is elaborated. The aim is to provide a reference for the prevention and control of biofilm in order to better guarantee food quality and safety.